La V heurística en el aprendizaje de ciencias sociales en estudiantes de segundo grado en la I.E.P.S.M. º 60025, Belén 2019 - Schlamauss Pastrana, Harold (2022)
The present study answers to the low results in the census evaluations obtained in Social Science area, especially in rural zones, with the objective of evaluating the effect of the “V” heuristic in the Social Science Learning in second-year high school students of IEPSM Nº 60025, Belén 2019. The study employs an experimental approach, employing a quasi-experimental design consisting of an experimental and a control group, each comprising a sample of 16 students. The results obtained after applying the strategy show that the V heuristic improves the Social Science Learning with an average rise from 2.69 (Pretest) to 12.37 (Post Test) by the experimental group on a scale of 0 to 20. Similar results were also obtained with respect to the indicator that constructs historical interpretations, ranging from 1.56 (Pretest) to 3.94 (Post Test) on a scale of 0 to 5; Furthermore, the responsible management of space and the environment rose from 0.30 (Pretest) to 4.56 (Post Test) on a scale of 0 to 9; Also, in responsibly management of economic resources rose from 1.00 (Pretest) to 3.88 (Post Test) on a scale of 0 to 6. The study concludes that the V heuristic improves significantly the Social Science Learning and Indicators by a p-value = 0.000 < ?=0.05.